(untitled) (Pedagogy of Higher and Secondary Education, 2022)
Article is devoted to definition of the purposes and maintenances (contents) of technological practice of studenis of faculties ofpreparation of teachers of labour training in conditions of step higher edtucation which has contiuous character and provides efective jormation at them corresponding the comperence.